The growth and valuation of generic skills - Dickerson, A; Green, F (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2002)
This paper investigates changes in the use of generic skills in Britain's workplaces, and examines which generic skills may be having an impact on wages over and above traditional human capital indicators such as education and work experience. We use instruments borrowed and adapted from commercial psychology to derive quantitative measures of generic skills used. The analysis shows that: (a) with the exception of physical skills, most generic skills are becoming more important in Britain's workplaces. Computing skills especially stand out as expanding rapidly. Thus the diffusion of computing technology has not reached saturation point; (b) both high-level communication skills and computing skills carry positive wage premia, controlling fo all other indicators of skill, conventiona or otherwise. Moreover, advanced and complex usages of computers earn a higher premium than more straightforward usage. This finding differs from earlier findings based on individual longitudinal data for France in the 1980s and later for Germany. The difference can be attributable to the richer skills data afforded to us, or to our applying it in the context of Britain's flexible labor markets at a (different) time with rapid diffusion of computing technology. The computing effect remains when we analyse within-cohort changes between 1997 and 2001; (c) over and above the impact of the job-holder's actual job tasks, the extent to which the establishment's work force uses computers raises pay. Together with b), this finding suggests that computing may be having an effect on the way structure in Britain; (d) other generic skills are also significantly associated with pay, some positively and some negatively, but these associations may not reflect causal effects. The change-within-cohorts estimates are not precise enough to be sure that any of these other skills have significant causal impacts on pay; (e) there are significant differences, as one might expect, between the generic skills in jobs held by men and by women. However, these differences do not contribute to accounting for any of the unexplained gender pay gap that is conventionally attributed to discrimination.